Esterification of free fatty acids in simulated waste cooking oil using sulphuric acids as catalyst: pre-treatment of feedstock for biodiesel production - Amir Lukmanhisyam, Haili (2014)
Oil has been a major contribution in the world energy supply nowadays. As fossil fuel become exhausted every day, alternative fuel like biodiesel which sustainable and renewable has become potential substitute. Majority biodiesel are made from vegetable oil but create imbalance to food supply chain. In order to avoid this problem, waste cooking oil has been discovered as a very prospective and cheap feedstock for biodiesel. The objective of this study is to learn the batch kinetic esterification of waste cooking oil using Sulphuric acids as catalyst over a wide range of methods by evaluating the a few parameters such as the stirring speed, the effect of temperature condition and methanol to oil molar ratio.Simulated waste cooking oil with 5% free fatty acids is prepared by adding oleic acid into virgin oil to be use as feedstock for this study. The experiment will be done using methanol as the solvent by manipulating the oil and methanol ratio, varying the stirring speed or revolutions per minute (rpm), and changing the temperature. The best result found at 150 minutes of the experiment is with oil and methanol molar ratio of 1:15, 600 rpm stirring speed and temperature 60°C as the optimum condition for the pre-treatment of feedstock for biodiesel production.